Chondrosarcoma of the Temporomandibular Joint: A Case Report - Thamyryz Rafaela Almeida Simões; Lais de Oliveira Melo; Marcio Tadashi Tino; Gilberto Fenelon das Neves (Oral Surgery, 2026)
ABSTRACT Objective Tumours affecting the temporomandibular joint (TMJ) are rare and may mimic common temporomandibular disorders, leading to delayed diagnosis. This study reports a case of TMJ chondrosarcoma initially presenting with long‐standing TMJ symptoms. Methods A 56‐year‐old female presented with right preauricular pain during mouth opening, closing and mastication for approximately 10 years. Clinical examination revealed a maximum interincisal opening of 20 mm with pain in the right TMJ. Cone‐beam computed tomography and magnetic resonance imaging demonstrated condylar and articular fossa alterations, including sclerosis, deformity, bone erosions and calcified intra‐articular loose bodies. The lesion was surgically resected en bloc with the articular disc while preserving the mandibular fossa. Histopathological analysis confirmed grade I chondrosarcoma. Written informed consent was obtained from the patient. Results Postoperatively, the patient showed improved mouth opening, reduced pain, preserved facial symmetry and no neurological deficits. Conclusion Accurate diagnosis of TMJ tumours requires careful clinical and imaging evaluation. Early recognition of malignant TMJ lesions can prevent delays in diagnosis and improve treatment planning and outcomes.